A deusa não conhece fronteiras e fala todas as línguas: um estudo sobre a religião Wicca nos estados unidos e no Brasil - Terzetti Filho, Celso Luiz (2016)
Created in England at the end of the first half of the twentieth century Wicca was widespread in the United States from the 60's, and in Brazil from the end of the 90s. Based on the works of the founder, Gerald B. Gardner, productions of American and Brazilian groups as well as field observations in Brazil and the United States, this study sought to identify the elements and ideas that contributed to the deterritorialization of religion and its reception in different contexts. Our thesis is that through the combination of two project identities Wicca previously restricted to a nationalist interpretation has been reoriented to a global context